Fermentation of Gembili Juice: Innovation in Functional Beverages Based on Lactobacillus plantarum B1765 - Amaliyah, Rohilatul Bidayah; Wikandari, Prima Retno (Jurnal Pijar Mipa, 2025)
Gembili tubers (Dioscorea esculenta) are abundant in Indonesia but remain underutilised despite their potential as a functional food. One effort that has been made is to produce a symbiotic fermented beverage, as it is known to contain prebiotic inulin that can be fermented using probiotics. Lactobacillus plantarum B1765 is charactherized by its probiotic potential. This research evaluated the impact of fermentation duration using L. plantarum B1765 starter culture on the quality of gembili juice products, including Total Lactic Acid Bacteria (LAB), pH, Total Titratable Acids (TTA), and organoleptic quality. Gembili juice was made by fermenting gembili juice at 37°C for 0, 6, 12, 18, 24, and 36 hours. The total LAB count was enumerated using the total plate count (TPC) method with MRS-Agar medium containing CaCO3. pH determination was performed using a pH meter. TTA was calculated by acid-base titration, and organoleptic quality was assessed by untrained panellists, who rated the level of liking using a hedonic scale. The total LAB and pH data were analyzed using the Kruskal–Wallis test, while the TTA data were analyzed using a one-way ANOVA to determine the significant differences among the fermentation durations. The fermentation time of gembili fermented beverages had an effect (p < 0.05) on the total number of LAB, pH, and TTA. LAB growth increased and reached an optimum of 7.55 x 10⁸ CFU/mL at 18 hours. However, the pH continued to decrease to 3.84, and the TTA continued to increase to 0.32% until the end of fermentation. Sensory evaluation (hedonic test) showed that fermentation time had no effect (p>0.05) on color and aroma. Still, it had an impact (p < 0.05) on taste, with the highest preference for the 18-hour fermentation. This product complies with SNI standards and is suitable for development as a fermented functional beverage. The inulin and phenolic compounds present in gembili may contribute to its antioxidant activity and α-glucosidase inhibitory effects.